current fraction = x/(x+1)
new fraction = (x+4)/(x+1 - 3)
= (x+4)/(x-2)
Their difference is 2 1/6 or 13/6
(x+4)/(x-2) - x/(x+1) = 13/6
multiply each term by 6(x+1)(x-2), the LCD
6(x+1)(x+4) - 6x(x-2) = 13(x+1)(x-2)
6x^2 + 30x + 24 - 6x^2 + 12x = 13x^2 -13x - 26
13x^2 - 55x - 50 = 0
solve using your favourite method of solving quadratics
You will get a whole number and a negative fraction.
I would just stick with the whole number answer.
The denominator of a fraction in the simplest form is greater than the numerator by 1. If 4 is added to the numerator, and 3 is subtracted from the denominator, then the fraction itself is increased by 2 1/6 . Find the original fraction.
8 answers
yes that might work but not rly helpful
Answer is not right...
wrong
Yo all!
Here is the answer to the question.
1/6
You're all welcome
Here is the answer to the question.
1/6
You're all welcome
x/x+1= Original fraction
x+4/x-2=x/x+1+13/6
6x/6x+6+13x+13=x-4/x-2
19x+13/6x+6=x+4/x-2
(cross multiply)
6x^2+20x+24=19x^2-25x-26
55x+50=13x^2
13x^2-55x-50=0
x=5
original fraction=5/6
x+4/x-2=x/x+1+13/6
6x/6x+6+13x+13=x-4/x-2
19x+13/6x+6=x+4/x-2
(cross multiply)
6x^2+20x+24=19x^2-25x-26
55x+50=13x^2
13x^2-55x-50=0
x=5
original fraction=5/6
Anonymous's answer, 5/6 is the right answer, ignore all of the others
bro nobdy be writing answers cmon guys